Impact of Service Quality on Customer Trust, Purchase Intention and Store Loyalty, with mediating role of Customers’ Satisfaction on Customer Trust and Purchase Intention - Khalaf Alharthey, Bandar (British Journal of Marketing Studies, 2019)
Service Quality is most important dimension on which customer satisfaction is based. The main theme behind this research paper is to examine the impact of Service Quality on Customer trust, Purchase Intention and Store Loyalty where Satisfaction performs the role of mediator with Trust and Purchase Intention. Also, this study will analyze the impact of Store image on store Loyalty.  This study is conducted mainly under the context of Grocery shopping in Jeddah, Saudi Arabia. Sample of 322 has been taken by using convenient sampling. Results show that all predicted hypothesis has been accepted after conducting the regression test. Positive impact has been seen between service quality and trust, service quality and purchase intention, and service quality and store loyalty. Also mediating role of customer satisfaction has been seen on customer trust and purchase intention. Finding also reveals that store image positively impact the store loyalty. This study will be helpful for researchers for future consideration in Saudi Arabia which provide useful implications as well.